TAT-Ngn2 Enhances Cognitive Function Recovery and Regulates Caspase-Dependent and Mitochondrial Apoptotic Pathways After Experimental Stroke - Zhao, Yu; Wang, Jinling; Du, Jiwei; Li, Baixiang; Gou, Xingchun; Liu, Jiannan; Hou, Lichao; Sang, Hanfei; Deng, Bin (Frontiers in Cellular Neuroscience, 2018)
Neurogenin-2 (Ngn2) is a basic helix-loop-helix (bHLH) transcription factor that contributes to the identification and specification of neuronal fate during neurogenesis. In our previous study, we found that Ngn2 plays an important role in alleviating neuronal apoptosis, which may be viewed as an attractive candidate target for the treatment of cerebral ischemia. However, novel strategies require an understanding of the function and mechanism of Ngn2 in mature hippocampal neurons after global cerebral ischemic injury. Here, we found that the expression of Ngn2 decreased in the hippocampus after global cerebral ischemic injury in mice and in primary hippocampal neurons after oxygen glucose deprivation (OGD) injury. Then, TAT-Ngn2, which was constructed by fusing a transactivator of transcription (TAT) domain to Ngn2, was effectively transported and incorporated into hippocampal neurons after intraperitoneal injection and enhanced cognitive functional recovery in the acute stage after reperfusion. Furthermore, TAT-Ngn2 alleviated hippocampal neuronal damage and apoptosis, and inhibited the CytC leak from the mitochondria to the cytoplasm through regulating the expression levels of BDNF, pTrkB, Bcl-2, Bax and cleaved caspase-3 after reperfusion injury in vivo and in vitro. These findings suggest that the downregulation of Ngn2 expression may have an important role in triggering brain injury after ischemic stroke and that the neuroprotection of TAT-Ngn2 against stroke might involve the modulation of BDNF-TrkB signalling that regulates caspase-dependent and mitochondrial apoptotic pathways, which may be an attractive therapeutic strategy for cerebral ischemic injury.